Evaluation of Novel Cognitive Assessment System for Testing Visual Memory of the Elderly - Lin, Chih-Lung; Chu, Ting-Ching; Wu, Meng-Hsuan; Deng, Ming-Yang; Chiu, Wen-Ching; Chen, Chien-Hsu; Sung, Pi-Shan; Tsao, Wen-Lung; Lin, Tsung-Chih (IEEE access, 2021)
With the development of such technologies as embedded systems, cloud databases and hardware components, detection of cognitive in the elderly can be made more convenient and accurate. This work develops a novel cognitive assessment interactive embedded system, which consists of a micro-controller unit (MCU), organic light-emitting diode (OLED) modules and a client identification circuit. The reliability of the proposed system is demonstrated in visuospatial memory tests. With its combination of OLED modules and pressable components, the elderly can use the system to perform testing under a flashing light source sequence with tactile feedback. To identify the various pattern arrangements in the Corsi block tapping task (CBTT), the client identification circuit in the proposed system is implemented to compute the number of OLED lighting devices on each column of the wooden base. The data that are collected from each subject will be transferred to cloud servers through a smart phone APP via wireless networks to eliminate recording errors by the experimenter. The functionality of the spatial working memory is verified in experiments that involve the proposed OLED, a computerized version of the CBTT, and 24 participants. Experimental results reveal that the difference in memory span between young and elderly groups is significant, F(1, 92) = 214, p<0.001, indicating the feasibility of the proposed system in spatial working memory detection.